2006
DOI: 10.1177/000348940611500201
|View full text |Cite
|
Sign up to set email alerts
|

Singer's Dystonia: First Report of a Variant of Spasmodic Dysphonia

Abstract: Singer's dystonia is a previously undescribed neurologic disorder that should be understood by those who treat voice performers and voice disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 7 publications
1
20
0
2
Order By: Relevance
“…Given that the neural circuits responsible for the control of speaking and singing potentially overlap, our findings suggest that these regional alterations, too, reflect a commonly affected voice‐specialized modality across different forms of laryngeal dystonia. Clinically, these findings support evidence showing that the phenomenology of laryngeal TSFDs is often interlocked: the majority of SD patients report their singing being affected similar to speaking, whereas SLD patients gradually develop SD symptoms …”
Section: Discussionsupporting
confidence: 81%
“…Given that the neural circuits responsible for the control of speaking and singing potentially overlap, our findings suggest that these regional alterations, too, reflect a commonly affected voice‐specialized modality across different forms of laryngeal dystonia. Clinically, these findings support evidence showing that the phenomenology of laryngeal TSFDs is often interlocked: the majority of SD patients report their singing being affected similar to speaking, whereas SLD patients gradually develop SD symptoms …”
Section: Discussionsupporting
confidence: 81%
“…Laryngeal adductor dystonia is the predominant form of spasmodic dysphonia described in professional singers [71]. It manifests as mid-range loss of singing voice due to strain, roughness and loss of vibrato.…”
Section: Other Instrumentsmentioning
confidence: 99%
“…However, considering the postoperative tendency for the intensity to increase, it is better to set the voice as very slightly breathy or weak rather than optimal. Chitkara et al reported that singer's dystonia is a previously undescribed variation of spasmodic dysphonia that affects the singing voice [11]. Most of these patients were found to display adductor hyperfunction in the mid range of the singing voice, producing straining, fatigue, roughness, and loss of vibration [11].…”
Section: Discussionmentioning
confidence: 99%